THE EFFECT OF JIGSAW II TOWARD LEARNING MOTIVATION AND READING COMPREHENSION AT THE SECOND GRADE OF ENGLISH STUDENTS IN STKIP DHARMA BAKTI - melati, eka (Jurnal Ipteks Terapan, 2014)
In teaching Reading, learning motivation and reading comprehension are essential. Ideally, after students learn the reading skills, both of their learning motivation and reading comprehension are better than before. In fact, the students still face some problems in comprehending the text. The problems are: they got low score of reading comprehension, they are lack of motivation, they are lack of vocabulary mastery, their reading achievement is still low, and the lecturer always uses small group discussion method without any variation. The purpose of this research was to find out the effect of JIgsaw II on learning motivation and reading comprehension.This study was an experimental research. Poupulation of this research was the second grade students of English Department of STKIP Dharma Bakti Lubuk Alung academic year 2010/2011 who was totally 133 students. The sample was selected by cluster random technique. The instruments were questionnaire of learning motivation and test of reading comprehension. The data were analyzed manually by t-test formula.The result of this study were learning motivation of students who were taught by Jigsaw II was better than those who were taught by small group discussion; and reading comprehension of students who taught by Jigsaw II was better than those who taught by small group discussion. It concluded that Jigsaw II produced better result on learning motivation and reading comprehension. It was implied that Jigsaw II could be used as method of teaching reading for English students.Doi: 10.22216/jit.2014.v8i2.211Â